Customer Satisfaction in the Restaurant Industry; Examining the Model in Local Industry Perspective - Sabir, Raja Irfan; Irfan, Muhammad; Akhtar, Naeem; Pervez, Muhammad Abbas; Rehman, Asad ur (Journal of Asian Business Strategy, 2014)
Customer satisfaction plays a pivotal role in success of every business organization whether it is meant for a product or a service. Every business needs not only to retain its current customers but also to expand customer’s base significantly and it is possible only when target customer is fully satisfied from company on some parameters. The objective of study is to construct comprehensive model of customer satisfaction in fast growing restaurant industry covering all the major dimensions of concept. Secondary research and Quantitative techniques were used to explain the concept of customer satisfaction. Stratified random sampling was used for this purpose for data analysis purpose, Correlation and multiple regressions while using SPSS-16 were used to test the model. This research will add in existing base of knowledge on vast topic of customer satisfaction while focusing on local restaurant industry.